Diseño e implementación de un sistema de gestión académica e integración con un entorno de realidad virtual de aprendizaje para el colegio particular a distancia "Amazonas " de la ciudad de Loja. - Espinosa Cueva, Carla Elizabeth (2013)
The present end of career project is focused on the development of an Academic Management System integrated with a Virtual Reality Learning Environment for the private distance school "Amazonas" in the city of Loja. The Academic Management System (SGA) is a Web application whose objective is to offer the institution administrators the services of accounts administration, students’ and teachers’ management, enrollment and tuition fees payment administration, students’ enrollment, attendance administration, grades and other activities regarding the students’ administration of the school. It also offers the students and representatives the possibility to have access to their academic profile via Internet. As software development methodology for the SGA, XP was used (Extreme Programming) and the development pattern used was MVC (Controlled View Model). The SGA was implemented in PHP5 using the framework Codeigniter 2.1, a template was used for the system interface based in CSS3 and Bootstrap to improve the design of the graphic interface. And the manager of the database used was MySql 5.5. The Virtual Reality Environment (ERVA) is focused on providing support as a technological tool in the different courses created for the students of such institution, a tridimensional space was designed so that students and teacher can interact in real time through the representation of an avatar. For the ERVA, a Moddle was chosen as web platform, Second Life as virtual worlds platform and to interconnect both platforms, Stoodle was used. For the configuration and design of the virtual classroom of the school, and for it to be accessible from the web, a piece of ground was purchased in the server of Second Life, where the 3D objects that Stoodle offers were configured to interact with the available tools in Moodle such as: chat, glossary of terms, forums, readings, presentations and questionnaires.